Pengenalan & Pelatihan “Fast Math Tricks” Bagi Siswa Sekolah Dasar Jemaat GMIT Petra Kefamenanu - Justin Eduardo Simarmata; Merlin Helentina Napitupulu; Thresia Trivict Semiun; Maria Wisrance Wihelmina (LPPM UNIVERSITAS DIAN NUSWANTORO, 2021)
Introduction and training of “Fast Math Tricks” for elementary school students in GMIT Petra Kefamenanu congregation aims to develop students' thinking skills and interest in mathematics. This community service activity is carried out for one month, with a meeting duration of 90 minutes per meeting. Students who take part in the activity are students who are considered capable of participating in the training, come from the sixth grade of elementary schools in the GMIT Petra Kefamenanu congregation. The method of implementing this activity is the method of testing, lecturing, and practice. The activity began with an introduction to